Battery, preparation method thereof and power utilization device

By introducing elastic components into all-solid-state lithium-ion batteries, the solid contact is improved, and the problems of degraded battery performance and high pressure requirements are solved, and the cell performance improvement and usage scenario expansion are achieved.

CN119905702APending Publication Date: 2025-04-29BEIJING ELECTRIC VEHICLE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411995575.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The solid contact mode in all-solid-state lithium-ion batteries seriously limits the transmission capacity of ions and electrons at the interface, resulting in a degradation of battery performance and requires high pressure to achieve close contact, which is unbearable by existing battery packs.

Method used

The elastic components are added inside the battery, and by compressing and assembling the pole unit and the elastic components into the housing, a tight battery cell structure is formed, reducing internal resistance and improving battery cell performance.

Benefits of technology

By improving solid contact, reducing internal resistance of the battery cell, improving battery cell performance, expanding usage scenarios, and simplifying the battery preparation process and reducing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119905702A_ABST
    Figure CN119905702A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of batteries, and particularly discloses a battery, a preparation method of the battery and a power utilization device. The at least one pole group unit is accommodated in the shell and comprises a negative plate, an electrolyte membrane and a positive plate, and the electrolyte membrane is arranged between the positive plate and the negative plate; the at least one elastic component is accommodated in the shell, and is arranged between the adjacent pole group units and / or between the pole group units and the shell; wherein the elastic assembly is in a compressed state. Therefore, according to the battery, the solid-solid contact problem is improved, the internal resistance of the battery core is reduced, the application range and application scene are expanded, and industrial use is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of battery technology, and specifically relates to a battery and a preparation method thereof and an electrical device. Background Art

[0002] Lithium-ion batteries have become the mainstream energy storage technology with their high energy density, long cycle life, and good battery chemical stability. Driven by the large-scale application of electric vehicles around the world, lithium-ion batteries have experienced rapid development in the past decade. However, existing liquid lithium-ion batteries are approaching their energy density limit and have safety issues such as flammability, explosion and leakage, which pose serious safety risks to electric vehicles and other energy storage applications. Therefore, driven by the demand for high energy density, high safety and long life batteries, all-solid-state batteries are regarded as an innovative technology to accelerate the popularization of electric vehicles. All-solid-state lithium-ion batteries are composed of positive electrodes, negative electrodes and solid electrolytes. Solid electrolytes (SEs) use non-flammable and volatile fast ion conductor materials, which can not only transmit lithium ions but also prevent electron transmission, eliminating safety hazards such as battery smoke and fire. On the basis of ensuring high safety and high specific energy, all-solid-state batteries have certain potential advantages in power characteristics, temperature adaptability and other aspects, and are expected to greatly improve the competitiveness of electric vehicles in terms of driving range and charging, and are the next generation of disruptive batteries. However, the solid-solid contact mode in all-solid-state batteries seriously affects the transmission capacity of ions and electrons at the interface, resulting in a decrease in battery performance, which is a major challenge in the current development and application of all-solid-state batteries.

[0003] In order to improve solid-solid contact, researchers have adopted a variety of strategies. One method is to modify the surface of the electrode and electrolyte to increase their surface compatibility and adhesion. For example, by coating a layer of material with good compatibility with the electrolyte on the surface of the electrode to improve contact. Another method is to optimize the preparation process of the electrode and electrolyte to obtain a more uniform and close contact. For example, high temperature and high pressure treatment is used. These two strategies improve the problem of solid-solid contact from the perspectives of material modification and preparation process improvement, respectively. Despite this, all-solid-state batteries still need to be applied to a pressure of several hundred megapascals during use to allow the inside of the electrode and the electrode and electrolyte to be in close contact and to exert the performance of the battery cell. At present, the pressure on the battery pack is only a few megapascals, and the pressure of several hundred megapascals cannot be achieved in the battery pack, that is, the all-solid-state battery cannot be assembled for application. Therefore, the solid-solid contact problem in all-solid-state batteries needs to be further improved. Summary of the invention

[0004] This application is based on the inventor's discovery and understanding of the following facts and problems:

[0005] Solid-solid contact in all-solid-state batteries refers to the solid-solid "point-to-point" physical contact mode between the positive electrode, electrolyte and negative electrode. Since both the solid electrolyte and the electrode materials are solid, the contact area and contact tightness between them are often not as good as the contact between the liquid electrolyte and the electrode in the liquid battery. Solid-solid contact severely limits the transmission capacity of ions and electrons at the interface of all-solid-state batteries, and as the battery charging and discharging process continues, the positive and negative electrodes repeatedly undergo phase changes and volume changes, which further deteriorates the physical contact between the positive and negative sides of the all-solid-state battery, causing a sharp decline in battery performance. Poor solid-solid contact may lead to a series of problems, including large interface impedance, reduced battery performance and charge and discharge efficiency. For example, during the charge and discharge process, increased resistance may lead to increased energy loss, reducing the actual available energy of the battery. Secondly, the poor mechanical stability of the interface leads to local high current density and stress, causing local overheating and unstable battery performance. For example, the failure of the lithium metal negative electrode contact leads to the formation of lithium dendrites, affecting the safety of the battery cell.

[0006] The present application aims to solve at least one of the technical problems in the related art to a certain extent. To this end, the present application proposes a battery and a preparation method thereof to solve the solid-solid contact problem, reduce the internal resistance of the battery cell, and expand the application scenarios.

[0007] The first aspect of the present application provides a battery, comprising:

[0008] case;

[0009] At least one electrode group unit, the electrode group unit is contained in the housing, and comprises a negative electrode sheet, an electrolyte membrane and a positive electrode sheet, wherein the electrolyte membrane is disposed between the positive electrode sheet and the negative electrode sheet;

[0010] At least one elastic component, which is accommodated in the housing and is disposed between adjacent pole group units and / or between the pole group unit and the housing;

[0011] Wherein, the elastic component is in a compressed state.

[0012] The present application improves the solid-solid contact problem, reduces the internal resistance of the battery cell, improves the performance of the battery cell, expands the use scope and application scenarios of the battery cell, and is conducive to industrial use.

[0013] In some embodiments, the ratio of the thickness of the elastic component after being compressed in the housing to the thickness to which the elastic component can be compressed ranges from 10% to 80%.

[0014] In some embodiments, the elastic modulus of the elastic component is 10 MPa to 1000 MPa.

[0015] In some embodiments, the thickness of the elastic component is 10 μm to 16 mm.

[0016] In some embodiments, the elastic component includes at least one of a polymer organic object and a metal object.

[0017] In some embodiments, the material of the polymer organic object includes at least one of thermoplastic elastomer and rubber; in some embodiments, the material of the metal part includes at least one of titanium alloy and steel, and the structure of the metal part includes at least one of trapezoidal, Z-shaped and funnel-shaped. Thus, elasticity can be provided to the elastic component.

[0018] In some embodiments, the shell includes at least one of an aluminum shell and a steel shell; the shell has a wall thickness of 0.2 mm to 2 mm, thereby providing a shell with a certain strength as an outer shell.

[0019] The second aspect of the present application provides a method for preparing a battery, comprising:

[0020] Providing elastic components;

[0021] Combining the negative electrode sheet, the electrolyte membrane and the positive electrode sheet into an electrode group unit;

[0022] Combining the negative electrode sheet, the electrolyte membrane and the positive electrode sheet into an electrode group unit;

[0023] The electrode group unit and the elastic component are stacked in the cavity of the lower shell, and a cover plate is put on, and the cover plate is pressed to contact the lower shell, and the cover plate and the lower shell are sealed to obtain a battery.

[0024] The distance from the stacking height to the edge of the shell is less than the maximum downward pressure distance that the elastic component can support, and the elastic force of the elastic component after compression is less than the pressure resistance of the shell.

[0025] The above method of the present application has a simple operation process and a short preparation cycle, which reduces cost consumption. The prepared solid-state battery does not need to be used under high temperature and high pressure, which simplifies the battery use method, expands the battery's use range and application scenarios, and is conducive to industrial use.

[0026] The third aspect of the present application provides an electrical device, which is the battery described in the first aspect of the present application or the battery prepared by the method described in the second aspect of the present application. The electrical device has all the features and advantages of the batteries described above, which will not be described one by one here. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 It is a schematic diagram of the structure of the battery of the embodiment of the present application.

[0028] Figure 2 It is a structural schematic diagram of the trapezoidal elastic component of the present application.

[0029] Figure 3 It is a structural schematic diagram of the Z-shaped elastic component of the present application.

[0030] Figure 4 It is a structural schematic diagram of the funnel-shaped elastic component of the present application.

[0031] Reference numerals:

[0032] 1-shell; 2-elastic component; 3-electrolyte membrane; 4-positive electrode sheet; 5-negative electrode sheet. DETAILED DESCRIPTION

[0033] The embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present application, but cannot be understood as limiting the present application.

[0034] The first aspect of the present application provides a battery, referring to Figure 1 The battery comprises: an electrode group unit, a shell 1 and an elastic component 2, wherein the electrode group unit is accommodated in the shell and comprises a positive electrode sheet 4, a negative electrode sheet 5 and an electrolyte membrane 3; wherein the electrolyte membrane is arranged between the positive electrode sheet and the negative electrode sheet, and the elastic component is accommodated in the shell and arranged between adjacent electrode group units and / or between the electrode group unit and the shell; the elastic component is in a compressed state.

[0035] The present application improves the solid-solid contact problem, reduces the internal resistance of the battery cell, improves the performance of the battery cell, expands the use scope and application scenarios of the battery cell, and is conducive to industrial use.

[0036] In some embodiments, the ratio of the thickness of the elastic component after compression in the shell to the thickness to which the elastic component can be compressed ranges from 10% to 80%, for example, it can be 10%, 20%, 30%, 40%, 50%, 60%, 70% or 80%, etc., and different compression amounts can be selected according to design requirements.

[0037] In some embodiments, the elastic modulus of the elastic component is 10 MPa to 1000 MPa, for example, 10 MPa, 50 MPa, 100 MPa, 300 MPa, 400 MPa, 500 MPa, 600 MPa, 700 MPa, 800 MPa, 900 MPa or 1000 MPa, etc. The elastic modulus is selected according to the size of the battery cell and the battery cell system.

[0038] In some embodiments, the thickness of the elastic component is 10 μm to 16 mm, for example, 10 μm, 20 μm, 50 μm, 100 μm, 500 μm, 1 mm, 2 mm, 5 mm, 10 mm, 15 mm or 16 mm, etc. It should be noted that the thickness is the thickness of the elastic component after compression, which is about 10% to 80% of the thickness before compression. The thickness of the elastic component is selected according to the size of the battery cell and the different battery cell systems.

[0039] In some embodiments, the elastic component includes at least one of a polymer organic object and a metal object.

[0040] In some embodiments, the material of the polymer organic object includes at least one of a thermoplastic elastomer and rubber; in some embodiments, the material of the metal piece includes at least one of a titanium alloy and steel, and the structure of the metal piece may be a trapezoid (for details, see Figure 2 ), Z-shaped (for details, please refer to Figure 3 ) or funnel-shaped (for details, please refer to Figure 4 ). In this way, the elastic component can have better elasticity, and the elastic component can maintain a certain compression state in the battery, which can buffer and absorb the poor contact problem caused by the volume change of the electrode, thereby making the solid-solid interface contact closer.

[0041] In some embodiments, the shell material is the same metal or composite metal that can be laser welded, such as an aluminum shell or a steel shell. The shell includes a lower shell and a cover plate, and the wall thickness of the shell is 0.2mm to 2mm, for example, it can be 0.2mm, 0.4mm, 0.6mm, 0.8mm, 1mm, 1.2mm, 1.4mm, 1.6mm, 1.8mm or 2mm. The present application uses a shell with a certain strength as the outer shell, and uses laser welding to seal it, which can ensure that the inside of the battery is in a positive pressure state.

[0042] It can be understood that there is no particular limitation on the specific type of the battery, which may be a primary battery, a secondary battery (including but not limited to a lithium-ion battery, a sodium-ion battery, etc.); the shape of the battery may be a cylindrical battery, a square battery, or a battery of any other shape, etc.

[0043] Typically, a solid-state battery includes a positive electrode sheet, a negative electrode sheet, and an electrolyte membrane, wherein the positive electrode sheet, the negative electrode sheet, and the electrolyte membrane can be made into an electrode group unit by winding or lamination process, and the electrode group unit and the elastic component described in the present application can be contained in an outer package. During the battery charging and discharging process, active ions are embedded and detached back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte membrane is arranged between the positive electrode sheet and the negative electrode sheet, which mainly plays the role of preventing the positive and negative electrodes from short-circuiting, and at the same time allows active ions to pass through.

[0044] In some embodiments, the positive electrode sheet includes a positive electrode active material, a conductive agent, a binder, a solid electrolyte, and a positive electrode current collector.

[0045] In some embodiments, the preparation process of the positive electrode sheet can be dry or wet. The wet binder is polyvinylidene fluoride (PVDF), and the dry binder is polytetrafluoroethylene (PTFE), etc.

[0046] In some embodiments, the positive electrode active material can be lithium iron phosphate, a lithium nickel cobalt manganese (aluminum) oxide (Li(Ni x Co y M (1-x-y) )O, where M can be Mn or Al, 0 < x < 1, 0 < y < 1), a lithium-rich manganese-based material (xLi 2 MnO 3 ·(1 - x)LiMnO 2 (M = Ni, Co, Mn; 0 < x < 1)), lithium cobalt oxide, lithium manganese oxide, etc.; it can also be a sodium ion positive electrode material such as a layered oxide (Na x MO 2 , where M is a transition metal element such as Fe, Co, Ni, Mn, Cr, Ti, etc.), a Prussian blue compound (Na x M[M’(CN) 6 y·zH 2 O, where M and M’ represent transition metals such as Fe, Co, Ni, Mn, Cu, Zn, etc. and polyanion compounds).

[0047] In some embodiments, the positive electrode current collector can be a copper foil or a composite current collector.

[0048] In some embodiments, the shape of the positive electrode sheet can be circular or rectangular.

[0049] In some embodiments, the negative electrode sheet includes a negative electrode active material, a conductive agent, a binder, a solid electrolyte, and a negative electrode current collector.

[0050] In some embodiments, the preparation process of the negative electrode sheet can be dry or wet. The wet binder is carboxymethyl cellulose - sodium / lithium (CMC - Na / Li) and styrene - butadiene rubber (SBR), and the dry binder is polytetrafluoroethylene (PTFE), etc.

[0051] In some embodiments, the negative electrode active material can be graphite, silicon and its compounds, lithium titanate compounds, or lithium metal.

[0052] In some embodiments, the conductive agent is one or a mixture of a dot shape (such as carbon black, Super P, etc.), a linear shape (such as carbon nanotubes), and a sheet shape (such as graphene).

[0053] In some embodiments, the negative electrode sheet current collector may be copper foil, aluminum foil, or a composite current collector of copper foil and aluminum foil.

[0054] In some embodiments, the shape of the negative electrode sheet can be circular or rectangular.

[0055] In some embodiments, the electrolyte membrane in the positive electrode sheet and the negative electrode sheet can be a sulfide electrolyte membrane, a halide electrolyte membrane, an oxide electrolyte membrane or a polymer electrolyte membrane, etc., or it can be a composite membrane of two or more electrolytes, and the composite membrane can contain polymers and inorganic substances.

[0056] The second aspect of the present application provides a method for preparing a battery, comprising:

[0057] S1: Provide elastic components.

[0058] S2: Combine the negative electrode sheet, the electrolyte membrane and the positive electrode sheet into an electrode group unit.

[0059] Specifically, the negative electrode sheet, the electrolyte membrane and the positive electrode sheet can be stacked or wound and pressurized in sequence to form a pole group unit, and the elastic component is placed between the complete pole group units and used alone or in combination of multiple units.

[0060] S3: stacking the electrode group unit and the elastic component in the cavity of the lower shell, covering with a cover plate, pressing the cover plate to contact with the lower shell, and sealing the cover plate and the lower shell to obtain a battery.

[0061] The distance from the stacking height to the edge of the shell is less than the maximum downward pressure distance that the elastic component can support, and the elastic force of the elastic component after compression is less than the pressure resistance of the shell.

[0062] The third aspect of the present application provides an electrical device, which is the battery described in the first aspect of the present application or the battery prepared by the method described in the second aspect of the present application. The electrical device has all the features and advantages of the batteries described above, which will not be described one by one here.

[0063] In some embodiments, the battery can be used as a power source for the electrical device or as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0064] The embodiments of the present application are described in detail below.

[0065] Example 1

[0066] LiFePO 4As the positive electrode active material, Li 7 P 3 S 11 As solid electrolyte, carbon nanotubes as conductive agent, polyvinylidene fluoride as binder, with a mass ratio of 80:10:6:4, a positive electrode slurry is made and evenly coated on aluminum foil, and dried to obtain a positive electrode sheet;

[0067] Select sulfide solid electrolyte Li 7 P 3 S 11 The mixture is uniformly mixed with polytetrafluoroethylene as a binder at a mass ratio of 95:5, and an electrolyte membrane is obtained by multi-stage rolling;

[0068] Graphite as negative electrode active material, Li 7 P 3 S 11 As solid electrolyte, Super P as conductive agent, styrene-butadiene rubber and carboxymethyl cellulose as binder, anode slurry was prepared in a mass ratio of 85:10:1:2:2, and the anode slurry was evenly coated on copper foil and dried to obtain anode sheet;

[0069] The positive electrode sheet, negative electrode sheet and electrolyte membrane are then pressed together and cut into the set size to form an electrode unit. They are then wrapped with an insulating film together with a 10mm thick elastic component thermoplastic polyurethane TPU and placed in an aluminum shell. The elastic component is 5mm higher than the edge of the shell. The cover is then pressed flush with the shell and sealed by laser welding to obtain a solid-state battery.

[0070] Example 2

[0071] Ternary NCM811 as positive electrode active material, Li 10 G 2 S 12 As solid electrolyte, carbon nanotubes as conductive agent, polyvinylidene fluoride as binder, with a mass ratio of 85:10:2:3, a positive electrode slurry is made and evenly coated on aluminum foil, and dried to obtain a positive electrode sheet;

[0072] Select sulfide solid electrolyte Li 10 G 2 S 12 The mixture is uniformly mixed with polytetrafluoroethylene as a binder at a mass ratio of 95:5, and an electrolyte membrane is obtained by multi-stage rolling;

[0073] Silicon carbon as negative electrode active material, Li 10 G 2 S 12As solid electrolyte, carbon nanotubes as conductive agent, styrene-butadiene rubber and carboxymethyl cellulose as binder, a negative electrode slurry is prepared in a mass ratio of 90:05:1:2:2, and the slurry is evenly coated on copper foil and dried to obtain a negative electrode sheet;

[0074] The positive electrode sheet, negative electrode sheet and electrolyte membrane are then pressed together and cut into the set size to form an electrode unit. They are then wrapped with an insulating film together with a 10mm thick elastic component thermoplastic vulcanized rubber TPV and placed in a steel shell. The elastic component is 7mm higher than the edge of the shell. The cover is then pressed flush with the shell and sealed by laser welding to obtain a solid-state battery.

[0075] Example 3

[0076] LiCoO 2 As the positive electrode active material, Li 3.25 Ge 0.25 P 0.75 S 4 As solid electrolyte, carbon nanotubes as conductive agent, polytetrafluoroethylene as binder, with a mass ratio of 85:10:2:3, a positive electrode slurry is made and evenly coated on aluminum foil, and dried to obtain a positive electrode sheet;

[0077] Select sulfide solid electrolyte Li 3.25 Ge 0.25 P 0.75 S 4 The mixture is uniformly mixed with polytetrafluoroethylene as a binder at a mass ratio of 95:5, and an electrolyte membrane is obtained by multi-stage rolling;

[0078] Graphite as negative electrode active material, Li 3.25 Ge 0.25 P 0.75 S 4 As solid electrolyte, Super P as conductive agent, styrene-butadiene rubber and carboxymethyl cellulose as binder, anode slurry was prepared in a mass ratio of 85:10:1:2:2, and the anode slurry was evenly coated on copper foil and dried to obtain anode sheet;

[0079] The positive electrode sheet, negative electrode sheet and electrolyte membrane are then pressed together and cut into the set size to form an electrode unit. They are then wrapped with an insulating film together with an 8mm thick elastic component fluororubber FR and placed in an aluminum shell. The elastic component is 5mm higher than the edge of the shell. The cover is then pressed flush with the shell and sealed by laser welding to obtain a solid-state battery.

[0080] Example 4

[0081] Lithium-rich manganese-based positive electrode LRM is used as the positive electrode active material, Li 3 YC 6As solid electrolyte, carbon nanotubes as conductive agent, polytetrafluoroethylene as binder, with a mass ratio of 87:6:4:3, a positive electrode slurry is made and evenly coated on aluminum foil, and dried to obtain a positive electrode sheet;

[0082] Select halide solid electrolyte Li 3 YC 6 The mixture is uniformly mixed with polytetrafluoroethylene as a binder at a mass ratio of 90:10, and an electrolyte membrane is obtained by multi-stage rolling;

[0083] Pure silicon is used as the negative electrode active material and polyvinylidene fluoride is used as the binder, and a negative electrode slurry is prepared at a mass ratio of 90:10, which is evenly coated on a copper foil and dried to obtain a negative electrode sheet;

[0084] The positive electrode sheet, negative electrode sheet and electrolyte membrane are then pressed together and cut into the set size to form an electrode unit. They are then wrapped with an insulating film together with a 12mm thick elastic component silicone rubber SR and placed in a steel shell. The elastic component is 7mm higher than the edge of the shell. The cover is then pressed flush with the shell and sealed by laser welding to obtain a solid-state battery.

[0085] Example 5

[0086] Lithium-rich manganese-based positive electrode LRM is used as the positive electrode active material, Li 3 YC 6 As solid electrolyte, carbon nanotubes as conductive agent, polytetrafluoroethylene as binder, with a mass ratio of 87:6:4:3, a positive electrode slurry is made and evenly coated on aluminum foil, and dried to obtain a positive electrode sheet;

[0087] Select halide solid electrolyte Li 3 YC 6 The mixture is uniformly mixed with polytetrafluoroethylene as a binder at a mass ratio of 90:10, and an electrolyte membrane is obtained by multi-stage rolling;

[0088] Lithium metal is used as the negative electrode active material, and the metal lithium negative electrode and copper foil are rolled to obtain a negative electrode sheet;

[0089] The positive electrode sheet, negative electrode sheet and electrolyte membrane are then pressed together and cut into the set size to form an electrode unit. They are then wrapped with an insulating film together with a 5mm thick elastic steel sheet and placed in an aluminum shell. The elastic component is 3mm higher than the edge of the shell. The cover is then pressed flush with the shell and sealed by laser welding to obtain a solid-state battery.

[0090] Comparative Example 1

[0091] The difference from Example 1 is that there is no elastic component. In this comparative example, the positive electrode sheet, the negative electrode sheet and the electrolyte membrane are pressed together, wrapped with an insulating film, and placed in an aluminum shell, covered with a cover plate, and sealed by laser welding to obtain a solid-state battery.

[0092] The remaining preparation method and parameters are consistent with Example 1.

[0093] Comparative Example 2

[0094] The difference from Example 2 is that there is no elastic component. In this comparative example, the positive electrode sheet, the negative electrode sheet and the electrolyte membrane are pressed together, wrapped with an insulating film, and placed in a steel shell, covered with a cover plate, and sealed by laser welding to obtain a solid-state battery.

[0095] The remaining preparation method parameters are consistent with Example 2.

[0096] Comparative Example 3

[0097] The difference from Example 3 is that there is no elastic component. In this comparative example, the positive electrode sheet, the negative electrode sheet and the electrolyte membrane are pressed together, wrapped with an insulating film, and placed in an aluminum shell, covered with a cover plate, and sealed by laser welding to obtain a solid-state battery.

[0098] The remaining preparation method and parameters are consistent with Example 3.

[0099] Comparative Example 4

[0100] The difference from Example 4 is that there is no elastic component. In this comparative example, the positive electrode sheet, the negative electrode sheet and the electrolyte membrane are pressed together, wrapped with an insulating film, and placed in a steel shell, covered with a cover plate, and sealed by laser welding to obtain a solid-state battery.

[0101] The remaining preparation method and parameters are consistent with Example 4.

[0102] Comparative Example 5

[0103] The difference from Example 5 is that there is no elastic component. In this comparative example, the positive electrode sheet, the negative electrode sheet and the electrolyte membrane are pressed together, wrapped with an insulating film, and placed in an aluminum shell, covered with a cover plate, and sealed by laser welding to obtain a solid-state battery.

[0104] The remaining preparation method and parameters are consistent with Example 5.

[0105] Comparative Example 6

[0106] The difference from Example 1 is that there is no elastic component and no shell restraint. In this comparative example, the positive electrode sheet, the negative electrode sheet and the electrolyte membrane are laminated together, and an aluminum-plastic film is inserted for sealing to obtain a solid-state battery.

[0107] The remaining preparation method and parameters are consistent with Example 1.

[0108] The test method is as follows:

[0109] (1) Internal resistance: discharge the cell to 50% SOC; let it stand for 1 hour and record the cell voltage V1; apply a current I pulse for 10 seconds and record the voltage V2 at 10 seconds. Calculate the internal resistance based on (V2-V1) / I.

[0110] (2) Constant current charging ratio: The battery cell is charged at 1C constant current and constant voltage to the upper cut-off voltage. The constant current charging capacity Q1 / total charging capacity Q is equal to the constant current charging ratio.

[0111] The following table shows the internal resistance test results of the embodiments and comparative examples.

[0112] Table 1 Test results

[0113]

[0114] From the data results of the five control groups, namely, Example 1 and Comparative Examples 1 and 6, Example 2 and Comparative Example 2, Example 3 and Comparative Example 3, Example 4 and Comparative Example 4, and Example 5 and Comparative Example 5, it can be seen that the internal resistance of the solid-state battery provided by the present application is significantly reduced, and the constant current charging ratio is significantly increased compared with the battery without elastic components and hard shell constraints.

[0115] To summarize, the present application adds an elastic component inside the battery cell to restrain the electrode group unit and the elastic component in a non-deformable shell in a positive pressure manner. On the one hand, the elastic component can play a buffering role, absorb the volume change caused by the expansion and contraction of the electrode material, enhance the mutual contact between the materials, greatly reduce the internal resistance of the battery cell, and is beneficial to the performance of the battery cell. Compared with the battery cell without elastic components, the internal resistance of the battery cell trial-produced in the present application is reduced by more than 25%, and the constant current charging ratio is increased by more than 10%; on the other hand, the self-restraint ability of the battery cell is increased, and the performance can be exerted without external pressure, which expands the use scenarios of the battery cell.

[0116] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example" or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0117] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in the field can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. A battery, characterized in that: include: case; At least one electrode group unit, the electrode group unit is contained in the housing, and comprises a negative electrode sheet, an electrolyte membrane and a positive electrode sheet, wherein the electrolyte membrane is disposed between the positive electrode sheet and the negative electrode sheet; At least one elastic component, which is accommodated in the housing and is disposed between adjacent pole group units and / or between the pole group unit and the housing; Wherein, the elastic component is in a compressed state.

2. The battery according to claim 1, characterized in that The ratio of the thickness of the elastic component after being compressed in the shell to the thickness to which the elastic component can be compressed is in the range of 10% to 80%.

3. The battery according to claim 1, characterized in that The elastic modulus of the elastic component is 10MPa to 1000MPa.

4. The battery according to claim 1, characterized in that The thickness of the elastic component is 10 μm to 16 mm.

5. The battery according to claim 1, characterized in that The elastic component includes at least one of a polymer organic object and a metal object.

6. The battery according to claim 5, characterized in that The material of the high molecular organic object includes at least one of thermoplastic elastomer and rubber.

7. The battery according to claim 5, characterized in that The material of the metal part includes at least one of titanium alloy and steel; and / or The structure of the metal part includes at least one of a trapezoidal shape, a Z-shape, and a funnel shape.

8. The battery according to claim 1, characterized in that The housing comprises at least one of an aluminum housing and a steel housing; and / or The wall thickness of the shell is 0.2 mm to 2 mm.

9. A method for preparing a battery according to any one of claims 1 to 8, characterized in that: include: Providing elastic components; Combining the negative electrode sheet, the electrolyte membrane and the positive electrode sheet into an electrode group unit; The electrode group unit and the elastic component are stacked in the cavity of the lower shell, and a cover plate is put on, and the cover plate is pressed to contact the lower shell, and the cover plate and the lower shell are sealed to obtain a battery.

10. An electrical device, characterized in that: A battery comprising the battery according to any one of claims 1 to 8 or a battery prepared by the method according to claim 9.